The Relationship Between Early Breastfeeding Initiation (EBI) and Bonding Attachment Between Mother and Newborn at the Bineh Krueng Health Center, Southwest Aceh Regency, in 2026 - Eka Ilhamni; Fera Sawita; Wirdayanti; Asmaul Husna; Suzanna Fitri (Athallah Publishing, 2026)
Early Breastfeeding Initiation (EBI) is an important early intervention in forming an emotional bond between mother and baby through skin-to-skin contact in the first hour of life. The implementation of EBI can increase bonding attachment which plays a role in children's emotional and psychological development. However, not all mothers carry out EBI optimally so that it can affect the quality of the mother-baby relationship. To determine the relationship between Early Breastfeeding Initiation (EBI) and bonding attachment between mother and newborn at the Bineh Krueng Health Center, Southwest Aceh Regency. This study is a quantitative research with an observational analytical design using a cross sectional approach. The population in this study is all mothers who give birth to newborns as many as 60 people. The sampling technique used the Slovin formula so that a sample of 60 respondents was obtained. Data analysis using the Chi-Square test. The results showed that most of the mothers carried out EBI as many as 41 respondents (68.3%) and had good bonding attachment as many as 39 respondents (65%). The results of the Chi-Square test showed a value of p = 0.002 (p < 0.05) which means that there is a significant relationship between EBI and bonding attachment between mother and newborn. There is a significant relationship between Early Breastfeeding Initiation (EBI) and maternal and newborn attachment bonding. It is hoped that health workers can improve education and assistance to mothers and families in the implementation of EBI so that it can be carried out optimally to support the formation of emotional bonds between mothers and babies.